Exploration of Mathematical Concepts in Oceanography: A Literature Review - Dodi, Dodi; Zibar, Zan (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
Mathematics is crucial in oceanography, enabling the modeling of complex ocean phenomena such as currents, waves, tides, and pollutant dispersion. This paper highlights the use of partial differential equations, numerical methods, and spatial statistics in simulating physical ocean processes. Key models include the Navier–Stokes equations for fluid flow, advection–diffusion models for pollutant transport, and wave models for ocean surface dynamics. These models are vital for practical applications like climate prediction, disaster mitigation, and marine ecosystem management. For example, modeling sea surface temperature aids in forecasting El Niño and La Niña events that impact rainfall and fisheries. In Indonesia, a maritime country highly exposed to ocean hazards, mathematical tools support marine research, policy planning, and sustainable development. This study presents an overview of mathematical models in oceanography, emphasizing their analytical strength and value in addressing environmental and resource challenges.